Soft power and hard choices: A critical perspective on health and inclusion in disadvantaged communities. (November 2019) - Clark, Julie; Jenkins, Nick; Noone, Sarah
The potential of area-based initiatives as a mechanism for addressing health inequities is coming increasingly to the fore within local policy and planning. The need to move beyond 'bricks and mortar' in order to mitigate and reverse concentrations of disadvantage is now well established within academic and policy discourse, yet plans to stimulate economic development may be of limited benefit to local communities without addressing poor population health. Drawing on attempts to introduce assets-based community development made by a health and social care partnership in Scotland, UK, this article explores the opportunities, risks and tensions that arise when statutory organisations seek to incorporate 'bottom up' approaches to community development within hierarchical organisational cultures. Those working within such structures frequently welcome more participatory approaches. However, syndicalist and co-operative models of health promotion risk dilution, as statutory organisations supporting more radical approaches to addressing the social determinants of health are forced to function within a context of increasingly strained public sector budgets.